Perseverative cognition and health behaviours: exploring the role of intentions and perceived behavioural control - McCarrick, Dane; Prestwich, Andrew; O'Connor, Daryl B. (Psychology & health, 2024)
Worry and rumination (Perseverative Cognition, PC) have been associated with health behaviours, but the underlying mechanisms are unknown. Given the role of physiological experiences on perceived behavioural control (PBC) and emotion regulation on intention-health behaviour relationships, we tested whether: PC prospectively predicts poorer health behaviours; PC moderates the relationship(s) between intentions/PBC and health behaviour, as well as whether the relationship between PC and health behaviour is mediated by intentions and PBC. In a prospective design, 650 participants (mean age = 38.21 years; 49% female) completed baseline measures of intentions, PBC and PC (worry and rumination) and 590 (mean age = 38.68 years; 50% female) completed follow-up (Time 2) measures of health behaviours (physical activity, sleep, sedentary activity, unhealthy snacking) 1-week later. Worry and rumination (at T1) predicted poorer sleep quality. Worry, but not rumination, moderated PBC-physical activity frequency relations. Consistent with mediation, the indirect paths from both worry and rumination, through PBC, to sleep quality and total sleep time were significant. PC is associated with poorer sleep quality and PBC can play a mediating role in such relationships. Future research should further consider the role that PBC plays in PC-health behaviour relations.